Design concept analysis of educational toys to stimulate early childhood fine motor development - Nurul Fitriana Bahri; Ica Ramawisari; Sheila Andita Putri (Institut Seni Indonesia Surakarta, 2023)
The early years of a child's life are widely acknowledged as a critical period for growth and development, encompassing significant advancements in their physical, cognitive, and emotional aspects. While development encompasses many different areas, fine motor skills are the cornerstone of a child's capacity to interact with their environment and attain significant achievements. This research discusses educational toys to stimulate fine motor development in early childhood. This research uses the theory of Palgunadi about design aspects, which are functional, aesthetic, and security of the product. This research aims to produce several alternative component designs that can be placed on a busy board to stimulate children's fine motor development. This research uses qualitative methods with data collection techniques through observation, interviews, and literature studies. The design method used in this research is SCAMPER. The results of this research are several alternative components of educational toy design that can be implemented on busy boards in order to optimize early childhood fine motor development. This research presents a comprehensive analysis of the design concept that underlies an educational toy to stimulate fine motor development in early children. The proposed toy provides a distinctive and captivating learning experience that effectively targets multiple aspects of fine motor skill development. This pioneering design contributes to the burgeoning collection of educational toys that are intentionally fashioned to foster skill-building in early children.